Diversity of Perspectives on Education and Inclusion (Revista Lusófona de Educação, 2025)
This issue of the Revista Lusófona de Educação brings together contributions that reflect the diversity of perspectives and issues traversing the contemporary educational field. The multiplicity of viewpoints presented invites readers to think of education as a space for inclusion, well-being, and renewal of practices — from early childhood to adulthood.Issue No. 67 opens with a critical reflection on the evolution of educational inequality in primary education in Portugal, questioning the effectiveness of public policies implemented over recent decades. The focus on social representations in the training of social educators reinforces the importance of understanding the symbolic frameworks that shape educational practices.The issue also includes studies centered on childhood: the analysis of children’s emotions in preschool physical education contexts and the study on promoting socioemotional skills in children with cerebral palsy underline the role of schools in building environments of well-being, inclusion, and holistic development. Complementarily, the ethnographic study of a children’s choir in Porto highlights the value of art and musical expression in fostering happiness and cultural citizenship.